Comprehensive insights into the prescribing trends of carbamazepine, lamotrigine, lithium, and valproate in the UK Primary Care from 1995 to 2018 - Siti Watiqah Samsuddin; Juan Carlos Bazo-Alvarez; Patricia Schartau; Irene Petersen (PLoS ONE, 2026)
Background Mood stabilisers carbamazepine, lamotrigine and valproate remain the cornerstone medication in the treatment of epilepsy, and in the management of psychiatric disorders alongside lithium. Prescribing decisions are influenced by patient’s preference, clinical history, and risk. This study examines mood stabiliser initiation and prevalence prescribing trends in UK primary care (1995–2018), stratified by sex (male and females) and age (18–39, 40–59, 60–79 and 80–99 years), irrespective of diagnosis. Method Cohort studies using UK anonymised electronic primary care data from IQVIA Medical Research Data (IMRD) of individuals aged 18–99 years registered with participating General Practice. Results Carbamazepine prescribing declined sharply across ages and sexes since the early 2000s. In contrast, lamotrigine prescribing increased markedly from 2005, thus becoming most initiated among individuals aged 18–39 years by 2018. Carbamazepine initiation predominated in individuals aged 40–99 years, and more so in females than males. Valproate initiation decreased throughout study period: (2018 vs 1995) adjusted Incidence Rate Ratio (aIRR) ranged from 0.12–0.44. However, prevalence rose in males (18–79 years) with adjusted Prevalence Rate Ratio (aPRR) ranged from 1.14–1.60, and females (40–79 years) at aPRR 1.12–1.31. By 2018, valproate was still prevalent among 18–39 years males (3.40/1000 individuals [3.19–3.61]) compared to females (1.18/1000 individuals [1.06–1.30]). Carbamazepine, lamotrigine and valproate were almost equally prescribed by 2018, while lithium the least prescribed. Mood stabiliser prescribing was higher among socioeconomically deprived individuals, both in terms of initiation and prevalence: (Townsend 5 vs Townsend 1) aIRR ranged from 1.07–3.26, and aPRR 1.17–2.90. Conclusion Over the study period across demographics, carbamazepine prescribing declined while lamotrigine prescribing increased substantially. By 2018, carbamazepine was mainly initiated in males and females aged 40–99 years and lamotrigine dominated in 18–39 years. Valproate initiation fell but remained prevalent in 18–39 years males; lithium prescribing remained low. Mood stabilisers were frequently prescribed in socioeconomically deprived individuals.